Idiopathic intracranial hypertension in pregnancy. (April 2014) - Thirumalaikumar, Lakshmi; Ramalingam, Kalaivani; Heafield, Tom
<x xml:space="preserve">Abstract</x> Key content Idiopathic intracranial hypertension is a rare condition that usually affects overweight women. It is a diagnosis of exclusion in a pregnant woman presenting with headache. It is important to understand the medical and surgical treatment options in pregnancy. The mode of delivery is usually decided by obstetric factors. The risk of visual impairment is the same in pregnant and non‐pregnant women with idiopathic intracranial hypertension. Learning objectives To identify how idiopathic intracranial hypertension presents in pregnancy. To know how to monitor and manage women with this condition during pregnancy. To understand the intrapartum, postpartum and long‐term implications of this condition. Ethical issues What is the extent of investigation before reaching the diagnosis of idiopathic intracranial hypertension? Do we need a high index of suspicion in all pregnant women presenting with headache? What is the preferred mode of delivery in idiopathic intracranial hypertension – do they all need a caesarean section?